ANTENNE RESEAU A COMMANDE DE PHASE - Touhami, N. Amar; Gueye, M.; Zakriti, A.; Boussouis, M.; Tribak, A. (European Scientific Journal, ESJ, 2013)
Phased array antennas are known for their capability to steer the beam pattern electronically with high effectiveness, managing to get minimum side-lobe levels and narrow beamwidths. Normally phase shifters are the devices in a phased array antenna that allow the radiated beam to be steered in the direction. The objective of this research is to investigate a phase shifter in a linear antenna array for angle scan. A microstrip antenna array is used since it is simple to design and fabricate. The phase shifter is provided using low pass filter. Ansoft Designer Software is used to simulate a low pass filter and Ansoft Ensemble Software to simulate phased array antenna